1993
DOI: 10.1007/bf00023469
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Israeli wild emmers to selected Australian pathotypes of Puccinia species

Abstract: Seedling responses to one Australian isolate of each of the stripe rust, stem rust and leaf rust pathogens were determined for 541 accessions of T dicoccoides collected from 23 locations in Israel . Resistance to stripe rust was more frequent than resistance to stem rust . Stripe rust responses showed a wide range of variability indicative of a number of genes for resistance . Comparisons of the present stem rust data and that reported for the same accessions tested in Israel indicated that different genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The present study in addition showed that emmer wheat accessions have better potential than durum accessions as sources of resistance to stem rust disease. Wild and cultivated emmer wheat from Israel (The et al 1993), and Nepal (Sharma et al 1995) were reported as good sources of resistance to rust diseases. The 24 selected accessions were resistant to most of the races of Pgt used in the study.…”
Section: Differentials/accessionsmentioning
confidence: 99%
“…The present study in addition showed that emmer wheat accessions have better potential than durum accessions as sources of resistance to stem rust disease. Wild and cultivated emmer wheat from Israel (The et al 1993), and Nepal (Sharma et al 1995) were reported as good sources of resistance to rust diseases. The 24 selected accessions were resistant to most of the races of Pgt used in the study.…”
Section: Differentials/accessionsmentioning
confidence: 99%
“…Wild emmer is a valuable source of stripe rust resistance (Gerechter-Amitai and Stubbs 1970;Nevo et al 1986a;The et al 1993). Gerechter-Amitai and Stubbs (1970) reported that accession G-25 from Rosh Pinna, Israel, was resistant to many races of P. striiformis from diVerent geographical origins and the gene responsible was later identiWed as Yr15 (Gerechter-Amitai et al 1989).…”
Section: Rust Resistancesmentioning
confidence: 99%
“…All the tested Mount Hermon accessions are highly resistant (Nevo et al, 1986 ;The et al, 1993). YrH52 is a temporarily designated stripe rust resistance gene harboured in the Mount Hermon accession H52, and has recently been mapped onto chromosome 1BS (Peng et al, 1999).…”
Section: Marker Enrichment and Chromosomal Localization For The Yrh52mentioning
confidence: 99%
“…They found that all the accessions from the Mount Hermon population were entirely immune to stripe rust at both seedling and adult stages, and accounted for 55 and 67% of the total highly resistant adult and seedling accessions, respectively. A study by The et al (1993) tested 541 accessions from 23 Israeli wild emmer populations using rust race 110 E143 Aj, and found that all accessions from the Mount Hermon population were highly resistant to stripe rust and accounted for 74% of the total highly resistant accessions. Van Silfhout et al (1989) tested about 850 wild emmer accessions collected from 31 locations using 28 stripe rust isolates from 19 countries, and found that 19 (28%) of the 68 promising resistant accessions derived from Mount Hermon.…”
mentioning
confidence: 99%